2002
DOI: 10.1021/jp0130416
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Characterization of Microporous Coordination Polymers with Open Frameworks

Abstract: The reactions of porous two-dimensional copper dicarboxylates (copper fumarate, copper terephthalate, copper styrene dicarboxylate, and copper 4,4‘-biphenyl dicarboxylate) with triethylenediamine as a pillar ligand yielded porous three-dimensional coordination polymers. The characterization by gas adsorption indicated that these coordination polymers have uniform micropores, high porosities, and gas adsorption capacities. These properties depend on the kind of dicarboxylate, and by changing it, the porosity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
0
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(160 citation statements)
references
References 38 publications
7
145
0
8
Order By: Relevance
“…Cu-MOF nanocrystals were synthesized in gram quantities by modifying published procedures [4,5] to control the water content in the reaction mixture, to reduce the synthesis time, and to improve reproducibility. The new procedure can be easily scaled up to larger quantities.…”
Section: Synthesis Of Cu-mofmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu-MOF nanocrystals were synthesized in gram quantities by modifying published procedures [4,5] to control the water content in the reaction mixture, to reduce the synthesis time, and to improve reproducibility. The new procedure can be easily scaled up to larger quantities.…”
Section: Synthesis Of Cu-mofmentioning
confidence: 99%
“…The simulated X-ray diffraction pattern of Cu-MOF presented by Seki [4,5] was used as a reference to verify the nature of the synthesized crystals (Figure 9a). X-ray diffraction of as-synthesized, semiactivated, and activated Cu-MOF nanocrystals (Figure 9b,c,d respectively) confirmed that both materials were Cu-MOF crystals and that the presumed 2D phase (Figure 9f,g), that results from the exposure to moisture or from an incomplete reaction, was not present.…”
Section: Cu-mof/matrimid ® Mixed-matrix Membranesmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs), as new materials, were applied in the field of gas storage, separation [1][2][3][4][5], heterogeneous catalysis [6], luminesce [7,8], and biomedicine [9][10][11]. There are many reports about the transition metal and the organic ligand, for example, N or O binding to Co(II), Cu(II), or Ni(II) [12]; the search for MOFs and new coordination polymers has attracted lots of researchers recently.…”
Section: Introductionmentioning
confidence: 99%
“…The field of metal-organic frameworks (MOFs) has grown explosively in recent years [1][2][3][4][5][6][7][8]; numerous studies have been reported owing to the potential applications of MOFs in gas storage [9][10][11][12][13][14][15], separation [16][17][18][19][20][21][22][23], luminescent materials [24][25][26][27][28][29][30][31][32], and heterogeneous catalysis [33][34][35][36][37][38][39][40][41]. While several MOFs have been discovered so far, only a few examples of chiral MOFs for enantiomer separations or heterogeneous asymmetric catalysis have been investigated [42].…”
Section: Introductionmentioning
confidence: 99%